The Covid-19 Pandemic Is Exposing the Plague of Neoliberalism (Praxis Educativa, 2020)
The current coronavirus pandemic is more than a medical crisis, it is also a political and ideological crisis. It is a crisis deeply rooted in years of neglect by neoliberal governments that denied the importance of public health and the public good while defunding the institutions that made them possible. We still have the opportunity to reimagine a world in which the future does not mimic the predatory neoliberal present. This should be a world that brings together the struggles for justice, emancipation and social equality. More urgent than ever is the need to struggle for a world that imagines and acts on the utopian promises of a just and democratic socialist society. In the face of the COVID-19 pandemic, matters of criticism, understanding and resistance are elevated into a matter of life or death. Resistance is a dire necessity.
Keywords: crisis; neoliberalismo; COVID-19; resistance; democracy